Unraveling the Novel Protective Effect of Patchouli Alcohol Against Helicobacter pylori-Induced Gastritis: Insights Into the Molecular Mechanism in vitro and in vivo - Lian, Da-wei; Xu, Yi-fei; Ren, Wen-kang; Fu, Li-jun; Chen, Fang-jun; Tang, Li-yao; Zhuang, Hui-ling; Cao, Hong-ying; Huang, Ping (Frontiers in Pharmacology, 2018)
Patchouli alcohol (PA), a natural tricyclic sesquiterpene extracted from Pogostemon cablin (Blanco) Benth. (Labiatae), has been found to exhibit anti-Helicobacter pylori and anti-inflammatory properties. In this study, we investigated the protective effect of PA against H. pylori-induced gastritis in vitro and in vivo, and determined the underlying mechanism. In the in vivo experiment, a C57BL/6 mouse model of gastritis was established using H. pylori SS1, and treatments with standard triple therapy or 5, 10 and 20 mg/kg PA were performed for 2 weeks. Results indicated that PA effectively attenuated oxidative stress by decreasing contents of intracellular reactive oxygen species (ROS) and malonyldialdehyde (MDA), and increasing levels of non-protein sulfhydryl (NP-SH), catalase and glutathione (GSH)/glutathione disulphide (GSSG). Additionally, treatment with PA significantly attenuated the secretions of interleukin 1 beta (IL-1β), keratinocyte chemoattractant and interleukin 6 (IL-6). PA (20 mg/kg) significantly protected the gastric mucosa from H. pylori-induced damage. In the in vitro experiment, GES-1 cells were cocultured with H. pylori NCTC11637 at MOI=100:1 and treated with different doses of PA (5, 10 and 20 μg/ml). Results indicated that PA not only significantly increased the cell viability and decreased cellular lactate dehydrogenase (LDH) leakage, but also markedly elevated the mitochondrial membrane potential and remarkably attenuated GES-1 cellular apoptosis, thereby protecting gastric epithelial cells against injuries caused by H. pylori. PA also inhibited the secretions of pro-inflammatory factors, such as monocyte chemotactic protein 1 (MCP-1), tumor necrosis factor-α (TNF-α) and IL-6. Furthermore, after PA treatment, the combination of NACHT, LRR and PYD domains-containing protein 3 (NLRP3) and cysteine-aspartic proteases 1 (CASPASE-1), the expression levels of NLRP3 inflammasome-related proteins, such as thioredoxin-interacting protein (TXNIP), pro-CASPASE-1, cle-CASPASE-1 and NLRP3 and genes (NLRP3 and CASPASE1) were significantly decreased as compared to the model group. In conclusion, treatment with PA for 2 weeks exhibited highly efficient protective effect against H. pylori-induced gastritis and related damages. The underlying mechanism might involve antioxidant activity, inhibition of pro-inflammatory factor and regulation of NLRP3 inflammasome function. PA exerted anti-H. pylori and anti-gastritis effects and thus had the potential to be a promising candidate for treatment of H. pylori-related diseases.